Once were warriors [videorecording (DVD)] - Owen, Rena, 1962-; Morrison, Temuera; Kerr-Bell, Mamaengaroa (Film Movement, 2016)
A husband's battle with alcholism causes him to have frequently terrifyingly erratic outbursts in front of his children and violent beatings to his wife.